Editorial - Girón-Pérez, Manuel Iván (Revista Bio Ciencias, 2016)
In this last number volumen 3, Revista Bio Ciencias creates a space related to the dissemination of technical – scientific knowledge related to regional important cultures in Mexico. Hence, two review manuscripts whose authors are part of the State University of Nayarit (Mexico) are presented, the first deals with the subject of potassium nutrition of Lychee (Litchi chinensis), a fruit original from the Asian continent but highly distributed in markets of high value in Mexico. The second review article discusses management factors (preharvest, harvest and postharvest) of Rosselle (Hibiscus sabdariffa L.), a plant widely cultured and distributed in our country, even though original from Africa.